Graphene Oxide-Silver Nanocomposite Induced Apoptosis in Human Hepatoma (HepG2) Cells Through Oxidative Stress and Caspase Dependent Signalling Pathway: GO-AG NANOCOMPOSITE INDUCED APOPTOSIS IN HEPG2 CELLS (Indian Journal of Engineering and Materials Sciences (IJEMS), 2023)
At present, the nanotechnology-based therapeutic agents have been emerged as the most reliable tool for various dangerous disorders including cancer. Liver cancer is one of the top five deadliest cancers. Hepatocellular Carcinoma (HCC) is the third most leading cause of death after lung and stomach cancer. Graphene Oxide, due to its unique chemical, mechanical, and optical properties, has offered a wide range of applications in biomedical fields. Silver nanoparticles can easily enter into mammalian cells, accumulate in the macrophages, and interact with biological molecules. In the present investigation, the effects of Graphene Oxide-Ag nanocomposites on human Hepatoma Cells (HepG2) have been investigated. Graphene oxide has been synthesised by modified Hummer’s method and further, Graphene Oxide-Ag nanocomposites have been prepared. The effect of nanoparticles on cell viability has been observed. For understanding the molecular pathway, the effects on oxidative stress (ROS and GSH levels), Caspase-3 Activity and Apoptotic Cell Population have been examined. Further, to confirm the role of oxidative stress and caspase-3 activity, the cell viability has been measured in the presence or absence of specific inhibitors. The results demonstrate that GO-Ag nanocomposites induce cytotoxicity, oxidative stress and apoptosis in HepG2 cells through caspase dependent pathway. The oxidative stress plays a crucial role in GO-Ag nanocomposites induced caspase dependent apoptosis. Thus, it can be concluded that GO-Ag nanocomposites show therapeutic efficacy in cancer cells.